Estado del arte de la caracterización de la biomasa residual de Lupinus mutabilis sweet y su propuesta metodológica. - Taipe Jaguaco, Sandra Janeth (2020)
A state of the art review of studies concerning the characterization of the residual chocho biomass (Lupinus mutabilis Sweet) resulting from the harvesting and post-harvesting process was carried out to develop a methodological guide that allows the determination of physical-chemical parameters of the chocho plant for reuse and formulate an environmental proposal matrix for the use of residual biomass. The research was based on the collection and bibliographic study, this process was carried out through the use of bibliographic collection sheets, analyzing a total of 120 scientific articles concerning study parameters such as: Lupinus mutabilis, dendrometric analysis, dry matter, alkaloids, phosphorus, potassium and nitrogen analysis, which include the potential processes of characterization of The biomass of Lupinus mutabilis Sweet. Therefore, a methodological guide with nine sections was designed to guide and provide the necessary tools to future research work in this field, for the characterization of residual biomass, possible execution in the laboratories of the Technical University of Cotopaxi and / or in laboratories easily accessible and moderate costs. Finally, in order to give the work an environmental value, a matrix of environmental proposals was developed in which 10 practices of the possible use of the residual biomass of Lupinus mutabilis sweet and environmental protection were carried out in such a way that it is used to recover, contribute, and improve the biological, physical and nutritional conditions of the soil.